Analisis Tingkat Kepuasan Mahasiswa Terhadap Kualitas Layanan dan Konten Musik pada Aplikasi Spotify - Muhammad Maigy Pratama; Nor Anisa (Majalah Ilmiah METHODA, 2025)
This study aims to evaluate student satisfaction with the Spotify music streaming application by examining two primary factors: service quality and music content. Using a quantitative survey approach, data were collected from university students who actively use Spotify for digital music consumption. The results show that most people who answered the survey (66.7%) think Spotify is easy to use and (70.4%) think it looks good. Also, 72.2% of users said that Spotify's features make their listening experience better, and 64.8% said that the audio quality is good. However, a notable proportion of respondents still experience errors or disturbances while using the application (57.4%). 57.4% of respondents think that music recommendations are usually good for their moods, and 55.6% think that being able to find new songs through recommendations is helpful. Overall satisfaction levels reached only 50%, indicating that Spotify has not fully met user expectations. These results indicate that there must be improvements in service quality, system stability, and recommendation accuracy to enhance overall user satisfaction among students.